Landmark Plastic Surgeon Advocacy within the Federal Government: Four Case Studies. Issue 5 (23rd December 2022) - Moss, Whitney; Pires, Giovanna; Reed, Evelyn; Crombie, Courtney; Janis, Jeffrey E.; Tenzel, Paul
Abstract : Background: Throughout history, plastic surgeons have advocated for the protection of the specialty and for better care for their patients. Whether through efforts to support and move legislation through Congress or through preventative advocacy in the form of lobbying against legislation, plastic surgeons have often used their expertise in the political sphere to shape patient care. We hope to inspire current and future plastic surgeons to be politically active and to devise ways in which their expertise can be used within the legislative system to better care for their patients. Methods: This article highlights four historical examples of plastic surgeon–led advocacy within the federal government: the U.S. Flammable Fabrics Act; the American Society of Plastic and Reconstructive Surgeons and the Federal Trade Commission, 1979; the Women's Health and Cancer Rights Act; and the Breast Cancer Patient Education Act. Results: We hope that plastic surgeons will—like Dr. Crikelair, Dr. Wider, and the members of American Society of Plastic Surgeons/American Society of Plastic and Reconstructive Surgeons—continue to play an active role in the shaping of the legislative system for our profession and, ultimately, our patients. Conclusions: To ensure the best care for their patients, plastic surgeons must continue to maintain their relationship with public health and legal professionals and legislators. Through relationships with patients and a firm understanding of their stories, plastic surgeons can have great impacts in all local, state, and national political spheres.